2020
DOI: 10.3390/nano10091708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fiber Posts on Stress Distribution of Endodontically Treated Upper Premolars: Finite Element Analysis

Abstract: By means of a finite element method (FEM), the present study evaluated the effect of fiber post (FP) placement on the stress distribution occurring in endodontically treated upper first premolars (UFPs) with mesial–occlusal–distal (MOD) nanohybrid composite restorations under subcritical static load. FEM models were created to simulate four different clinical situations involving endodontically treated UFPs with MOD cavities restored with one of the following: composite resin; composite and one FP in the palat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…Resin composites have evolved significantly over the last decades and now we are witnessing the greatest development of these materials [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Resin composites have evolved significantly over the last decades and now we are witnessing the greatest development of these materials [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the filler content resulted in an increase in the flexural modulus. Furthermore, an increase in the core materials’ modulus resulted in an increase in fracture resistance [ 26 ]. This could explain the findings of this study, as a previous paper showed that the stiffness of a core material within an elastic range could be indicated by the flexural modulus which, in turn, reflected the longevity and strength of the restoration.…”
Section: Discussionmentioning
confidence: 99%
“…Another finite element study [ 38 ] showed that the use of adhesive GFP was neither able to reduce the maximum stresses calculated on the occlusal surface nor to optimize the stress distribution regardless of different vertical post-approach. According to the authors, the placement of high amount of GFP can be deleterious to the remaining tooth structure without improving the mechanical response against chewing loading.…”
Section: Discussionmentioning
confidence: 99%
“…Although in vitro laboratory tests of extracted human teeth are important to obtain useful information about fracture load and the fracture mode, they are generally based on destructive experiments and have limited capacity to investigate the stress-strain relationship in the tooth restoration complex [ 38 , 39 ]. Therefore, 3D-FEA is an engineering tool that can be applied to biology, medicine and dentistry and used to investigate the mechanical behavior of complex systems by a mathematical approach and simulation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%